A Practical Guide to Plastics Sustainability : Concept, Solutions, and Implementation - Biron, Michel, author 551513; ScienceDirect (Online service) 7722 (Norwich : William Andrew, 2020)
A Practical Guide to Plastics Sustainability: Concept, Solutions, and Implementation is a groundbreaking reference work offering a broad, detailed and highly practical vision of the complex concept of sustainability in plastics. The book's aim is to present a range of potential pathways towards more sustainable plastics parts and products, enabling the reader to further integrate the idea of sustainability into their design process. It begins by introducing the context and concept of sustainability, discussing perceptions, drivers of change, key factors, and environmental issues, before presenting a detailed outline of the current situation with types of plastics, processing, and opportunities for improved sustainability. Subsequent chapters focus on the different possibilities for improved sustainability, offering a step-by-step technical approach to areas including design, properties, renewable plastics, and recycling and re-use. Each of these pillars are supported by data, examples, analysis and best practice guidance. Finally, the latest developments and future possibilities are considered.